2016
DOI: 10.1080/10498850.2014.994083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzyme Type on the Antioxidant Activities and Functional Properties of Enzymatic Hydrolysates from Sea Cucumber (Cucumaria frondosa) Viscera

Abstract: Effects of various proteases were obvious on the amino acid composition, antioxidant activities, and functional properties of enzymatic hydrolysates prepared from sea cucumber viscera (SCV). Alcalase, trypsin, and flavourzyme conferred better antioxidant activities on hydrolysates and endowed them with a higher degree of hydrolysis, coming to 19.08, 32.38, and 15.94%, respectively. For functional properties, neutrase-and flavourzymederived hydrolysates showed better foaming properties. Amino acid composition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…This indicates that CBMH has enhanced emulsifying properties compared to available commercial protein emulsifiers. These results were also higher than those found for common carp roe hydrolysates (Chalamaiahet al, 2015) and sea cucumber viscera (Yan et al, 2016).…”
Section: Resultscontrasting
confidence: 53%
“…This indicates that CBMH has enhanced emulsifying properties compared to available commercial protein emulsifiers. These results were also higher than those found for common carp roe hydrolysates (Chalamaiahet al, 2015) and sea cucumber viscera (Yan et al, 2016).…”
Section: Resultscontrasting
confidence: 53%
“…Profiling, DP and antioxidant activity of stone fish proteolysates A previous study has shown that the proteolysis of stone fish (A. lecanora) by alcalase could generate potential antioxidative proteolysates. [6] Park et al, [17] Yan et al [18] and Liceaga-Gesualdo and Li Chan [19] have also reported the advantages of using alcalase for generation of proteolysates, as it results in shorter peptides and reduced bitterness in addition to high antioxidant activity. Hence, in the current study, alcalase was used for digesting stone fish flesh for 8 h under optimum conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Sea cucumber is one of the most important holothurian species and popular seafood in East Asia. Due to its high protein, low fat, polysaccharides, and other nutrients, sea cucumber has been widely consumed as food and medicinal resources in several countries such as China, Japan, and South Korea (Han et al, ; Yan, Tao, & Qin, ). In China, the aquaculture of sea cucumber has expanded rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fish, there are also studies on the isolated protein from byproducts of triangle shell pearl mussel Hyriopsis cumingii (Liu, Zhou, Su, Li, & Li, ) and antarctic krill Euphausia superba (Wang et al, ). The previous studies of sea cucumber guts have mainly focused on endogenous proteases (Wu, Li, Zhu, Du, et al, ; Wu, Li, Zhu, Cheng, et al, ), protein hydrolysates (Han et al, ; Yan et al, ). However, the information about protein isolate from sea cucumber guts remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation